MACRO AND MICROECONOMIC INDICATORS ON BANKING CREDIT DISTRIBUTION IN INDONESIA - M. NadjibUsman (International Journal of Research Science and Management, 2018)
Changes in the level of people's business credit distribution are influenced by micro and macro-economic factors. This study aims to empirically examine the effect of loan to deporit ratio (LDR), capital adequacy ratio (CAR), non-performing loan (NPL), credit base interest rate (SBDK), BI rate and gross domestic product (GDP). The sample used is a national banking in Indonesia that distributes people's business loans. The research method uses multiple linear regression tests. The results of the study inform that non-performing loans, credit base rates and bank interest rates of Indonesia (BI rate) affect the distribution of bank credit. The study also informed that: loan to deporit ratio (LDR), capital adequacy ratio (CAR) and gross domestic product (GDP) had no effect on lending.